(3MGTjI Ydi CfhGQ GdJfRjd hCSQGQ GdJChjds - (3TjNj RGOg, YHO GdQMef Hf eMeO SdjeGf, J (B1078 (3g`s
(3ChdgG (B:s
(3jHOC gPg GdLRA ef ShQI GdfhQ YfO bhdg (B: (3Qhi GdEeGe GdhGMOj Yf gTGe Hf YQhI Yf CHjg Yf YGFTI QVj Gddg Yfge bGd bGd QShd Gddg Udi Gddg Ydjg hSde dG JfRdhgf GdZQa hdG JYdehgf GdcJGHIs
(3BNQgG (B:s
(3jfJgj YfO ShQI GdfGS YfO bhdg hGdeWdH aj GdShQI GdeJbOeI gj SdGeI GdHOf ef GdBaGJ GdePchQI haj gPg GdShQI SdGeI GdOjf ef hShSI GdTjWGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 332s
(3eYLe GdeDdajf (B2 / 111s
(3gOjI GdYGQajf (B1 / 549s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJaSjQ hYdhe GdbQBfs